HbA1c and the Risk of Lower Limb Ulcers Among Diabetic Patients: An Observational and Genetics Study - Guojun Guo; Yunlong Guan; Yuhuan Chen; Yuge Ye; Zeyu Gan; Xi Cao; Zhenbing Chen; Xingjie Hao (Journal of Diabetes Research)
Conclusions: High HbA1c levels increase the risk of lower limb ulcers in diabetic patients. MR analyses validated the positive but not significant association between genetically proxied HbA1c levels and lower limb ulcer risk. The results recommended an HbA1c goal of < 53 mmol/mol to decrease the incidence of diabetic ulcers.